Prospective trial of immuno(chemo)therapy before resection, definitive chemoradiotherapy or palliative therapy in patients with locally advanced or oligometastatic non-small cell lung cancer without a primary curative option. (October 2021) - Faehling, Martin; Fallscheer, Sabine; Kramberg, Sebastian; Sträter, Jörn; Eschmann, Susanne; Sätzler, Rainer; Heinzelmann, Frank
Abstract: Background: Recent phase II–III trials of immuno(chemo)therapy before resection in locally advanced resectable non-small cell lung cancer (NSCLC) report high rates of pathological response and promising survival. However, primarily, patients who did not undergo resection were excluded from these studies. Moreover, there are no data on chemoradiotherapy (CRT) after immuno(chemo)therapy in patients who are primarily not amenable to CRT. We hypothesised that induction immuno(chemo)therapy may enable patients with NSCLC with a potentially curative stage (III–IVA), for whom primary curative treatment (either resection or CRT) is not possible for anatomical or functional reasons, to receive curative treatment. Patients and methods: We enrolled 35 patients with NSCLC with aforementioned characteristics into a prospective real-world trial of induction immuno(chemo)therapy followed by morphologic and metabolic reassessment and multidisciplinary board-guided curative treatment (resection [preferred] or CRT) or palliative therapy. The primary end-point was the proportion of patients receiving curative treatment. Results: Thirty-two patients (91%) received curative treatment (11 resections and 21 CRT). 73% and 64% of patients who underwent resection had a major or complete pathological response, respectively. There were 14 recurrences: 2 (18%) in patients who underwent resection, 9 (43%) in patients who received CRT and 3 (100%) in patients who received palliative therapy (median follow-up 17 months). Eight tumour-related deaths occurred: 5 (24%) in patients who received CRT; and 3 (100%) in patients who received palliative therapy. There were no treatment-related deaths. Conclusions: In locally advanced or oligometastatic NSCLC without a primary curative option, induction immuno(chemo)therapy results in a high rate of curative treatment with promising early survival data. patients who underwent resection achieved a high rate of prognostically favourable pathological response. Highlights: Immunotherapy (IO) makes selected cases of palliative non-small cell lung cancer potentially curable. After IO, resection or chemoradiotherapy is feasible without enhanced toxicity. IO results in a high rate of complete pathologic response. Programmed-death ligand 1(PD-L1) predicts response and survival.